Changes in the growth rate of Chlamydomonas reinhardtii under long-term selection by temperature and salinity: Acclimation vs. evolution - Melero-Jiménez, Ignacio José; Bañares-España, Elena; García-Sánchez, María Jesús; Flores-Moya, Antonio; Melero-Jiménez, Ignacio José (Science of The Total Environment, 2022)
We investigated the roles of acclimation and different components involved in evolution (adaptation, chance and history) on the changes in the growth rate of the model freshwater microalga Chlamydomonas reinhardtii P. A. Dang. exposed to selective temperature and salinity. Three C. reinhardtii strains previously grown during one year in freshwater medium and 20 °C were exposed to 5 °C temperature increase and a salinity of 5 g L−1 NaCl. Cultures under each selective scenario and in combination (increase of salinity and temperature), were propagated until growth rate achieved an invariant mean value for 6 months (100–350 generations, varying as a function of scenario and strain). The changes of the growth rate under increased temperature were due to both adaptation and acclimation, as well as history. However, acclimation was the only mechanism detected under salinity increase as well as in the selective scenario of both temperature and salinity, suggesting that genetic variability would not allow survival at salinity higher than that to which experimental populations were exposed. Therefore, it could be hypothesized that under a global change scenario an increase in salinity would be a greater challenge than warming for some freshwater phytoplankton.
Keywords: Adaptación (Biología); Microalgas; Salinidad; Adaptation; Chance; Chlamydomonas reinhardtii; Historical contingency; Salinity; Temperature